Locus no cromossomo 19 influencia positivamente o número de oócitos recuperados em ciclos estimulados - Setti, Amanda Souza; Figueira, Rita de Cássia S.; Martinhago, Ciro Dresch; Braga, Daniela Paes de Almeida Ferreira; Iaconelli Jr., Assumpto; Edson Jr., Borges [UNESP] (Elsevier, 2011)
Objective: To evaluate if identified loci associated with normal age of menopause variation and early menopause can account for the poor response to controlled ovarian stimulation. Methods: A total of 71 patients, with age ≤ 35 years old, undergoing intracytoplasmic sperm injection were tested for three of the four newly identified genetic variants associated with normal variation in menopausal age and early menopause. Patients were divided into two groups: poor responder group (PR group, n=21) and normoresponder group (NR group, n=50). The influence of risk allele frequency on the response to controlled ovarian stimulation (COS) was evaluated. Logistic regression models were used. Results: There was no significant difference in the incidence of the genetic variants between NR and PR group. The risk allele for chromosome 19 variant (rs4806660) demonstrated a protective effect. The presence of a risk allele, either in homozygosis or in heterozygosis, was associated with an increased response to COS, resulting in an elevated number of follicles (Coef: 2.54, P= 0.041) and retrieved oocytes (Coef: 1.41, P= 0.041). Conclusions: Genetic variants rs244715, rs9379896 and rs4806660 are not risk factors for poor ovarian response. Instead, rs4806660 is associated with higher number of follicles and retrieved oocytes. It could be hypothesized that rs4806660 is associated with an increased response to gonadotrophin stimulus. © Todos os direitos reservados a SBRA - Sociedade Brasileira de Reprodução Assistida.
Locus at chromosome 19 positively influences the number of retrieved oocytes in stimulated cycles
Keywords: Assisted reproduction techniques; Biological markers; Controlled ovarian stimulation; Intracytoplasmic sperm injection; Single nucleotide polymorphisms; follitropin; gonadotropin; adult; blood sampling; chromosome 19; chromosome 5; chromosome 6; controlled ovarian stimulation; controlled study; cryopreservation; early menopause; female; female infertility; gene frequency; gene identification; gene locus; genetic association; genetic risk; genetic variability; genotype; heterozygosity; homozygosity; human; intracytoplasmic sperm injection; major clinical study; menopause; metaphase; oocyte retrieval; ovary follicle; ovulation induction; risk factor; single nucleotide polymorphism; treatment response